Agents and Artificial Intelligence 7th International Conference, ICAART 2015, Lisbon, Portugal, January 10-12, 2015, Revised Selected Papers - Duval, Béatrice; van den Herik, Jaap.; Loiseau, Stephane; Filipe, Joaquim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Conference on Agents and Artificial Intelligence, ICAART 2015, held in Lisbon, Portugal, in January 2015. The 18 revised full papers presented in this book were carefully reviewed and selected from 187 submissions. The papers are organized in two topical sections on agents and on artificial intelligence and focus on multi-agent systems and software platforms; distributed problem solving and distributed AI in general; knowledge representation; planning; learning; scheduling; perception; reactive AI systems; and evolutionary computing.
A Hybrid POMDP-BDI Agent Architecture with Online Stochastic Planning and Desires with Changing Intensity Levels -- Dynamic JChoc: A Distributed Constraints Reasoning Platform for Dynamically Changing Environments -- Stream X-Machines for Agent Simulation Test Case Generation -- Building Self-adaptive Systems by Adaptation Patterns Integrated into Agent Methodologies -- A Logic for Reasoning about Decision-Theoretic Projections -- Identifying Critical Positions based on Conspiracy Numbers -- Infinite Horizon Multi-Armed Bandits with Reward Vectors: Exploration / Exploitation Trade-off -- Solving PCSPs using Genetic Algorithms Guided by Structural Knowledge -- Activity Recognition for Dogs based on Time-series Data Analysis -- Machine Breakdown Recovery in Production Scheduling with Simple Temporal Constraints -- From Information Assistance to Cognitive Automation: A Smart Assembly Use Case -- A Heuristic for Constrained Set Partitioning in the Light of Heterogeneous Objectives -- Using Process Calculi for Plan Verification in Multiagent Planning -- Speeding Up Planning in Multiagent Settings using CPU-GPU Architectures -- LS2C - A Platform for Norm Controlled Social Computers -- Construction of a Planar PLCA Expression: A Qualitative Treatment of Spatial Data -- Offline Norm Evolution -- Parsing with Partially Known Grammar.
Keywords: Artificial intelligence; Optical data processing; Computers; Computer simulation; Artificial Intelligence; Computer Imaging, Vision, Pattern Recognition and Graphics; Theory of Computation; Information Systems and Communication Service; Simulation and Modeling